ROBOT ARM (ADVANCED RISC MACHINE) AUTOMATIC ITEMS TRANSFER BASED ON COLOR USING ARDUINO UNO R3 - Dedi Lesmana; Budy Satria; Yessi Ratna Sari (Universitas Islam Kuantan Singingi, 2020)
The latest evolution of technology lately had triggered a lot of creativity in our world,especially in robotic in industry. The use of a robot aims to save money and produces product with the same quality.The robot movers and goods is one of the implementation of technology in the field of robotics has the ability to help people to move goods from a place to place that has been made on the color of a grouping of the goods. In this research, robot was designed based on microcontroller 328. Also it is equipped with one DC motors as wheel driver, four servo motors as arm driver, one IR (Obstacle) sensor as an item detector and one TCS3200 sensors as colour.